2014
DOI: 10.1371/journal.pone.0086402
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Oscillations of Soybean Circadian Clock and Drought Responsive Genes

Abstract: Rhythms produced by the endogenous circadian clock play a critical role in allowing plants to respond and adapt to the environment. While there is a well-established regulatory link between the circadian clock and responses to abiotic stress in model plants, little is known of the circadian system in crop species like soybean. This study examines how drought impacts diurnal oscillation of both drought responsive and circadian clock genes in soybean. Drought stress induced marked changes in gene expression of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
106
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 80 publications
(128 reference statements)
17
106
0
Order By: Relevance
“…Transcription of GmLCL1 and GmLCL2 declined over the course of the day, and both of these genes were assigned to cluster 4 (Figure ). The transcription patterns of these genes match the patterns measured for chamber‐grown soybean (Liu et al., ; Marcolino‐Gomes et al., ).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Transcription of GmLCL1 and GmLCL2 declined over the course of the day, and both of these genes were assigned to cluster 4 (Figure ). The transcription patterns of these genes match the patterns measured for chamber‐grown soybean (Liu et al., ; Marcolino‐Gomes et al., ).…”
Section: Resultssupporting
confidence: 74%
“…Expression of several other circadian‐regulated genes has been studied in chamber‐grown soybean (Marcolino‐Gomes et al., ). Therefore, we aimed to compare these previous findings to expression patterns from field‐grown soybean.…”
Section: Resultsmentioning
confidence: 99%
“…Being very sensitive to drought, soybean productivity may be lost up to 40 % in years that suffer severe drought (Thao and Tran 2012). To improve drought tolerance of soybean cultivars, many studies have been carried out to identify useful genes, including TCS-related genes that might be employed in genetic engineering (Mochida et al 2010;Le et al 2011;Marcolino-Gomes et al 2014). Previous studies revealed that soybean genome contains at least 21 HKs, 13 HP and HP-like proteins, and 46 RRs/PRRs (Mochida et al 2010;Schmutz et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The clock controls a similar proportion of the transcriptome in rice, papaya, maize, soybean, and poplar (Zdepski et al, 2008;Hayes et al, 2010;Hoffman et al, 2010;Khan et al, 2010;Filichkin et al, 2011;Marcolino-Gomes et al, 2014). Genes subject to circadian clock regulation are central to many important physiological processes (Figure 1), including flowering time (Park et al, 1999;Yu et al, 2008), phytohormone synthesis and signaling Covington et al, 2008;Goodspeed et al, 2012), growth control (Nozue et al, 2007), metabolic activities (Gutierrez et al, 2008;Ni et al, 2009), abiotic stress responses (Legnaioli et al, 2009), and plant-pathogen interactions (Wang et al, 2011b).…”
Section: Introduction the Circadian Clockmentioning
confidence: 99%